Macrophage mannose receptor CD206-targeted PET imaging in experimental acute myocardial infarction - Andriana, Putri; Palani, Senthil; Liljenbäck, Heidi; Iqbal, Imran; Oikonen, Vesa; Virta, Jenni; Makrypidi, Konstantina; Rajander, Johan; Atencio Herre, Erika; Suni, Aino; Jalkanen, Sirpa; Knuuti, Juhani; et al. (Springer Science and Business Media LLC, 2025)
Background: The macrophage mannose receptor (CD206) is expressed predominantly on the surface of M2-type macrophages, which play a role in resolution of inflammation after myocardial injury. The purpose of this study was to evaluate the utility of CD206-targeted PET tracer Al[18F]F-NOTA-D10CM, a fluorinated mannosylated dextran derivative, for imaging immune responses after experimental acute myocardial infarction (MI).
Results: Flow cytometry revealed selective binding of Alexa-488-NOTA-D10CM to human M2-polarized macrophages derived from blood monocytes compared to M1 macrophages. The binding affinity of Al[18F]F-NOTA-DCM for CD206-positive Chinese hamster ovary cells was 1.83 ± 0.68 nM. In vivo PET and ex vivo autoradiography experiments in Sprague-Dawley rats studied at 3 and 7 days after permanent ligation of the left coronary artery or a sham-operation, showed significantly higher uptake of Al[18F]F-NOTA-DCM in the MI area than in remote areas, or the myocardium of sham-operated rats. However, there was no difference in uptake in the MI area between day 3 and day 7. Uptake of Al[18F]F-NOTA-DCM in the MI area correlated positively with the area-% of CD206-positive staining of the left ventricular myocardium (r = 0.481, P = 0.006). In vitro competition studies on tissue cryosections using a molar excess of unlabeled D10CM revealed a reduction of approximately 85%, confirming specific tracer binding.
Conclusion: Al[18F]F-NOTA-D10CM PET detects overexpression of CD206 after ischemic myocardial injury, and may be a suitable biomarker for detecting M2-type macrophages associated with the inflammatory process post-MI.